2018
DOI: 10.1002/path.5126
|View full text |Cite
|
Sign up to set email alerts
|

The c‐MYC–BMI1 axis is essential for SETDB1‐mediated breast tumourigenesis

Abstract: Characterising the activated oncogenic signalling that leads to advanced breast cancer is of clinical importance. Here, we showed that SET domain, bifurcated 1 (SETDB1), a histone H3 lysine 9 methyltransferase, is aberrantly expressed and behaves as an oncogenic driver in breast cancer. SETDB1 enhances c-MYC and cyclin D1 expression by promoting the internal ribosome entry site (IRES)-mediated translation of MYC/CCND1 mRNA, resulting in prominent signalling of c-MYC to promote cell cycle progression, and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 66 publications
(69 reference statements)
1
24
0
Order By: Relevance
“…Based on that MXD1 could inhibit MYC by competitively interacting with MAX, 18 we assumed that MAGI2‐AS3 could directly regulate MYC expression but this hypothesis was further overturned. Then, we found that overexpressed MAGI2‐AS3 declined the expressions of CDK4, CCND2 and BMI1 which were all regulated by MYC 28‐30 . Moreover it was confirmed that MAGI2‐AS3 could contribute MXD1 to bind with MAX but inhibit MYC to bind with MAX, which suggested that MAGI2‐AS3 suppress MYC by mediating MXD1.…”
Section: Discussionmentioning
confidence: 65%
“…Based on that MXD1 could inhibit MYC by competitively interacting with MAX, 18 we assumed that MAGI2‐AS3 could directly regulate MYC expression but this hypothesis was further overturned. Then, we found that overexpressed MAGI2‐AS3 declined the expressions of CDK4, CCND2 and BMI1 which were all regulated by MYC 28‐30 . Moreover it was confirmed that MAGI2‐AS3 could contribute MXD1 to bind with MAX but inhibit MYC to bind with MAX, which suggested that MAGI2‐AS3 suppress MYC by mediating MXD1.…”
Section: Discussionmentioning
confidence: 65%
“…Most of these previous studies were performed on transcriptome or gene levels. A recent study performed immunohistochemical staining (IHC) of SETDB1 in 43 BC tissues and showed a significant increase in the SETDB1 level in BC samples [13]. The present study further investigated the expression of SETDB1 by IHC and its clinical performance in a cohort of 159 patients with BC.…”
Section: Introductionmentioning
confidence: 80%
“…As a H3K9 methyltransferase, the physiological function of SETDB1 has been associated with gene silencing in mammalian development [5], particularly involving heterochromatin formation [6], stem cell maintenance [7], and endogenous retrovirus genes repression [8]. In the field of oncology, SETDB1 has been observed to be deregulated in various human carcinogenesis, including colorectal cancer, lung cancer, melanoma, and BC [9][10][11][12][13]. Moreover, abnormal expression of SETDB1 has been found to be a diagnostic biomarker of patient survival in the 2 major forms of human non-small cell lung carcinoma (adenocarcinoma and squamous cell carcinoma) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portions of the tumors were used for immunohistochemistry (IHC) to examine levels of Ki-67 (ab15580, Abcam, Cambridge, UK) and phosphorylated ERK1/2 (#4376, Cell Signaling, Danvers, MA). IHC was performed as previously described 15.…”
Section: Methodsmentioning
confidence: 99%